Development of an autonomous sea ice tethered buoy for the study of ocean-atmosphere-sea ice-snow pack interactions: the O-buoy - T. N. Knepp; J. Bottenheim; M. Carlsen; D. Carlson; D. Donohoue; G. Friederich; P. A. Matrai; S. Netcheva; D. K. Perovich; R. Santini; P. B. Shepson; W. Simpson; et al. (Atmospheric Measurement Techniques, 2010)
A buoy based instrument platform (the "O-buoy") was designed, constructed, and field tested for year-round measurement of ozone, bromine monoxide, carbon dioxide, and meteorological variables over Arctic sea ice. The O-buoy operated in an autonomous manner with daily, bi-directional data transmissions using Iridium satellite communication. The O-buoy was equipped with three power sources: primary lithium-ion battery packs, rechargeable lead acid packs, and solar panels that recharge the lead acid packs, and can fully power the O-buoy during summer operation. This system was designed to operate under the harsh conditions present in the Arctic, with minimal direct human interaction, to aid in our understanding of the atmospheric chemistry that occurs in this remote region of the world. The current design requires approximately yearly maintenance limited by the lifetime of the primary power supply. The O-buoy system was field tested in Elson Lagoon, Barrow, Alaska from February to May 2009, and deployed in the Beaufort Sea in October 2009. Here, we describe the design and present preliminary data.